2018
DOI: 10.1175/jhm-d-18-0027.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Skill of Medium-Range Ensemble Precipitation and Streamflow Forecasts from the Hydrologic Ensemble Forecast Service (HEFS) for the Upper Trinity River Basin in North Texas

Abstract: To issue early warnings for the public to act, for emergency managers to take preventive actions, and for water managers to operate their systems cost-effectively, it is necessary to maximize the time horizon over which streamflow forecasts are skillful. In this work, we assess the value of medium-range ensemble precipitation forecasts generated with the Hydrologic Ensemble Forecast Service (HEFS) of the U.S. National Weather Service (NWS) in increasing the lead time and skill of streamflow forecasts for five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…This error characteristic can be represented by allowing QPP model parameters to vary within a year (but not across years). This approach is common for predictions/forecasts at monthly to seasonal timescales (e.g., Bennett et al, 2017; Li et al, 2013; Woldemeskel et al, 2018) and has also been used in daily forecasting (e.g., Kim et al, 2018); Dynamic biases , that is, shifts in the mean of hydrological errors over longer time periods (e.g., month to year). These nonstationarities may be due to a range of factors including systematic errors in the hydrological model calibration data (e.g., Westra et al, 2014) and/or inability of hydrological model to capture changes in hydrological processes over longer time scales, for example, due to unusually wet/dry seasons, interannual climate variability, and/or changes in catchment properties (Coron et al, 2012; Fowler et al, 2016; Merz et al, 2011; Westra et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This error characteristic can be represented by allowing QPP model parameters to vary within a year (but not across years). This approach is common for predictions/forecasts at monthly to seasonal timescales (e.g., Bennett et al, 2017; Li et al, 2013; Woldemeskel et al, 2018) and has also been used in daily forecasting (e.g., Kim et al, 2018); Dynamic biases , that is, shifts in the mean of hydrological errors over longer time periods (e.g., month to year). These nonstationarities may be due to a range of factors including systematic errors in the hydrological model calibration data (e.g., Westra et al, 2014) and/or inability of hydrological model to capture changes in hydrological processes over longer time scales, for example, due to unusually wet/dry seasons, interannual climate variability, and/or changes in catchment properties (Coron et al, 2012; Fowler et al, 2016; Merz et al, 2011; Westra et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This error characteristic can be represented by allowing QPP model parameters to vary within a year (but not across years). This approach is common for predictions/forecasts at monthly to seasonal timescales (e.g., Bennett et al, 2017;Li et al, 2013;Woldemeskel et al, 2018) and has also been used in daily forecasting (e.g., Kim et al, 2018); 2. Dynamic biases, that is, shifts in the mean of hydrological errors over longer time periods (e.g., month to year).…”
Section: Introductionmentioning
confidence: 99%
“…We then disaggregate the predicted multidaily flow to daily flow using the granular patterns of daily flow in the bias-corrected model-simulated daily flow. The above approach is motivated by the fact that the larger the temporal scale of aggregation is, the more skillful a b k,1 is likely to be (Kim et al 2018;Limon 2019). Similar approaches have also been used in postprocessing forecasts of precipitation (Kim et al 2018;Schaake et al 2007a) and streamflow (Regonda and Seo 2008).…”
Section: B Multiscale Regressionmentioning
confidence: 99%
“…The positive impact of postprocessing raw model simulations of streamflow in ensemble streamflow forecasting has been widely reported (Kim et al 2018(Kim et al , 2016Madadgar et al 2014). Recently, it has also been shown that EnsPost significantly increases skill in ensemble forecasts of outflow from a water supply reservoir in North Texas during significant releases, in addition to that in ensemble inflow forecasts (Limon 2019).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation